Foreign direct investment in Malaysia: Trends and prospects - Mithani, Dawood Ali M.; Ahmad, Shabbir; Mohd Saifudin, Adam (World Business Institute, 2008)
This paper reports on a study analyzing recent trends, pattern and prospects of the foreign direct investment (FDI) in Malaysia in the post-1997 financial crisis period. Among the ASEAN-4 countries, Malaysia continues to remain as the main centre for attracting FDI.The macroeconomic variables such as GDP, exports and employment are found to be positively influenced by the growth of FDI in Malaysia. To enhance the positive effect of FDI on the growth process of the Malaysian economy the flow of FDI into export-oriented sector and use of domestic inputs by the foreign oriented firms need to be encouraged.It is suggested that for sustained flow of FDI, continual price stability, macroeconomic balances, good governance and economic liberalization reforms are crucially important in the country.In the event of declining inflows of FDI, Malaysia has to shiR towards inward looking policies and search other alternatives to sustain its growth and economic prosperity by seeking more investment oufflows as a global player.